Insight into an recommendations from three real-world laboratories. An Experience-Based Comparison. - Parodi, Oliver; Waitz, Colette; Bachinger, Monika; Kuhn, Rainer; Meyer-Soylu, Sarah; Alcántara, Sophia; Rhodius, Regina (Oekom, 2018)
Real-world laboratories (RwLs) as a new format within transdisciplinary science aim at promoting learning for and transformation towards sustainability. However, what are essential aspects to take into account while initiating and stabilizing such processes within RwLs? Comparing lessons learned of three German RwLs (BaWü Labs), we show that for establishing RwLs as melting pots for transdisciplinary research and societal transformation, four properties are crucial: an interior design that enables transdisciplinary research and intervention (in particular real-world experiments) based on a stable infrastructure; sustainability as guiding and operationalized principle for differentiating the format "RwL" from other labs; overarching research programs for assessing transformative effects of RwLs and didactic concepts suitable for RwL circumstances. Since RwLs mainly address a long-term cultural change, a long-term funding and research structure are essential as well.
Keywords: Nachhaltige Entwicklung; Wissenstransfer; Reallabor; Organisationsform; Fallbeispiel; Transdisziplinarität; Soziales Lernen